Thermal performance modeling of turbulent flow in multi tube in tube helically coiled heat exchangers. (January 2018) - Fouda, A.; Nada, S.A.; Elattar, H.F.; Refaey, H.A.; Bin-Mahfouz, Abdullah S.
Highlights: Heat transfer characteristics and performances of multi tubes in tube helically coiled heat exchangers. Parametric study for the effects of number of inner tubes and operating/geometrical parameters. Correlations for the performance indices in terms of operating/geometrical parameters. Abstract: Heat transfer characteristics and performances of a multi tubes in tube helically coiled ( MTTHC ) heat exchanger are numerically investigated. The effects of operating and geometrical parameters on the thermal and hydrodynamic performances of the coil are studied and presented for turbulent flow regimes. The current simulation model is compared and validated with available experimental results and a good agreement is obtained. The numerical results showed that, the overall heat transfer coefficient ( Uo ) enhanced by 23% and 28% with increasing Reynolds numbers of hot and cold water ( Rehw and Recw ) from 9000 to17000 and 14, 000 to 22, 000, respectively. Coil effectiveness ( ε ) increased by 28% and 60% with increasing coil diameter ( Dc ) from 100–150 mm and 100 to 250 mm, respectively and increased with 20% with increasing the number of inner tubes ( N ) from 1 to 5. Moreover, the maximum values of the thermal-hydrodynamic performance index and coil effectiveness occurs at N = 3. The coil pitch has slight effect on the coil performance. Comparisons between the presented MTTHC with concentric tube in tube helically coiled (CTTHC) and multi tubes in straight tube (MTST) heat exchangers are conducted and showed that MTTHC heat exchangers displayed higher thermal performance. General numerical correlations for thermal and hydraulic coil performance are developed within acceptable errors. Graphical abstract: Image, graphical abstract Physical model: (a) Geometry of multi tubes in tube helical coil, (b) Inner tubes configuration (c) section views of the studied coils.